cosh(3z)=i la ecuación
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Suma y producto de raíces
[src]
/ ____________\ / ____________\ / ____________\ / ___________\ / ___________\ / ___________\
5*pi*I |3 / ___ | pi*I |3 / ___ | pi*I |3 / ___ | pi*I |3 / ___ | pi*I |3 / ___ | 5*pi*I |3 / ___ |
- ------ + log\\/ -1 + \/ 2 / + - ---- + log\\/ -1 + \/ 2 / + ---- + log\\/ -1 + \/ 2 / + - ---- + log\\/ 1 + \/ 2 / + ---- + log\\/ 1 + \/ 2 / + ------ + log\\/ 1 + \/ 2 /
6 6 2 2 6 6
(((((log(3−1+2)−65iπ)+(log(3−1+2)−6iπ))+(log(3−1+2)+2iπ))+(log(31+2)−2iπ))+(log(31+2)+6iπ))+(log(31+2)+65iπ)
/ ___________\ / ____________\
|3 / ___ | |3 / ___ |
3*log\\/ 1 + \/ 2 / + 3*log\\/ -1 + \/ 2 /
3log(3−1+2)+3log(31+2)
/ / ____________\\ / / ____________\\ / / ____________\\ / / ___________\\ / / ___________\\ / / ___________\\
| 5*pi*I |3 / ___ || | pi*I |3 / ___ || |pi*I |3 / ___ || | pi*I |3 / ___ || |pi*I |3 / ___ || |5*pi*I |3 / ___ ||
|- ------ + log\\/ -1 + \/ 2 /|*|- ---- + log\\/ -1 + \/ 2 /|*|---- + log\\/ -1 + \/ 2 /|*|- ---- + log\\/ 1 + \/ 2 /|*|---- + log\\/ 1 + \/ 2 /|*|------ + log\\/ 1 + \/ 2 /|
\ 6 / \ 6 / \ 2 / \ 2 / \ 6 / \ 6 /
(log(3−1+2)−65iπ)(log(3−1+2)−6iπ)(log(3−1+2)+2iπ)(log(31+2)−2iπ)(log(31+2)+6iπ)(log(31+2)+65iπ)
/ / ___\ \ / / ___\ \
/ / ___\ \ / / ___\ \ / / ___\ \ / / ___\ \ |2*log\1 + \/ 2 / | |2*log\-1 + \/ 2 / |
\2*log\1 + \/ 2 / + pi*I/*\2*log\1 + \/ 2 / + 5*pi*I/*\2*log\-1 + \/ 2 / - pi*I/*\2*log\-1 + \/ 2 / - 5*pi*I/*|---------------- - pi*I|*|----------------- + pi*I|
\ 3 / \ 3 /
------------------------------------------------------------------------------------------------------------------------------------------------------------------
5184
5184(32log(−1+2)+iπ)(2log(−1+2)−5iπ)(2log(−1+2)−iπ)(32log(1+2)−iπ)(2log(1+2)+iπ)(2log(1+2)+5iπ)
(2*log(1 + sqrt(2)) + pi*i)*(2*log(1 + sqrt(2)) + 5*pi*i)*(2*log(-1 + sqrt(2)) - pi*i)*(2*log(-1 + sqrt(2)) - 5*pi*i)*(2*log(1 + sqrt(2))/3 - pi*i)*(2*log(-1 + sqrt(2))/3 + pi*i)/5184
/ ____________\
5*pi*I |3 / ___ |
z1 = - ------ + log\\/ -1 + \/ 2 /
6
z1=log(3−1+2)−65iπ
/ ____________\
pi*I |3 / ___ |
z2 = - ---- + log\\/ -1 + \/ 2 /
6
z2=log(3−1+2)−6iπ
/ ____________\
pi*I |3 / ___ |
z3 = ---- + log\\/ -1 + \/ 2 /
2
z3=log(3−1+2)+2iπ
/ ___________\
pi*I |3 / ___ |
z4 = - ---- + log\\/ 1 + \/ 2 /
2
z4=log(31+2)−2iπ
/ ___________\
pi*I |3 / ___ |
z5 = ---- + log\\/ 1 + \/ 2 /
6
z5=log(31+2)+6iπ
/ ___________\
5*pi*I |3 / ___ |
z6 = ------ + log\\/ 1 + \/ 2 /
6
z6=log(31+2)+65iπ
z6 = log((1 + sqrt(2))^(1/3)) + 5*i*pi/6
z1 = -0.293791195673181 - 2.61799387799149*i
z2 = -0.293791195673181 - 0.523598775598299*i
z3 = -0.293791195673181 + 1.5707963267949*i
z4 = 0.293791195673181 - 1.5707963267949*i
z5 = 0.293791195673181 + 0.523598775598299*i
z6 = 0.293791195673181 + 2.61799387799149*i
z6 = 0.293791195673181 + 2.61799387799149*i